Supreme Court in quest of identity - Dāsa, Gobinda, 1929- (Lucknow : Eastern Book Co., 2000)
On the Supreme Court of India, its powers and historic judgments, 1950-1986.
Keywords: India. -- Supreme Court -- History; Judicial review -- India -- History; Political questions and judicial power -- India -- History